Vaccination campaigns in remote areas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A divisional delegate for the Cameroon ministry responsible for livestock discusses the importance and difficulties of vaccination campaigns in remote areas.